2021
DOI: 10.1093/jn/nxab279
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Watermelon Juice Attenuates Acute Hyperglycemia-Induced Macro-and Microvascular Dysfunction in Healthy Adults

Abstract: Background Acute hyperglycemia reduces NO bioavailability and causes macro- and microvascular dysfunction. Watermelon juice (WMJ) is a natural source of the amino acid citrulline, which is metabolized to form arginine for the NO cycle and may improve vascular function. Objectives We examined the effects of 2 weeks of WMJ compared to a calorie-matched placebo (PLA) to attenuate acute hyperglycemia-induced vascular dysfunction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Ellis et al [ 9 ] observed that plasma ADMA was unaffected by ingestion of 360 mL watermelon juice twice a day (1.63 g of L-citrulline) for four weeks in healthy postmenopausal women. Two recent studies [ 8 , 9 ] did not observe significant increases in circulating L-arginine following watermelon supplementation, indicating that insufficient substrate for NO production may have contributed to the lack of improvement in FMD. Moreover, Shanely et al [ 27 ] demonstrated that 710 mL of watermelon puree (2.28 g of L-citrulline/L-arginine) for six weeks reduced sVCAM-1, but not soluble platelet selectin (sP-Selectin), high-sensitivity C-reactive protein (hs-CRP), and soluble intercellular adhesion molecule-1 (sICAM-1) in overweight and obese postmenopausal women.…”
Section: Evidence Of Watermelon Ingestion On Vascular Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…Ellis et al [ 9 ] observed that plasma ADMA was unaffected by ingestion of 360 mL watermelon juice twice a day (1.63 g of L-citrulline) for four weeks in healthy postmenopausal women. Two recent studies [ 8 , 9 ] did not observe significant increases in circulating L-arginine following watermelon supplementation, indicating that insufficient substrate for NO production may have contributed to the lack of improvement in FMD. Moreover, Shanely et al [ 27 ] demonstrated that 710 mL of watermelon puree (2.28 g of L-citrulline/L-arginine) for six weeks reduced sVCAM-1, but not soluble platelet selectin (sP-Selectin), high-sensitivity C-reactive protein (hs-CRP), and soluble intercellular adhesion molecule-1 (sICAM-1) in overweight and obese postmenopausal women.…”
Section: Evidence Of Watermelon Ingestion On Vascular Healthmentioning
confidence: 99%
“…Several previous studies have evaluated the effect of watermelon products on macro- and microvascular responsiveness assessed by brachial FMD and near-infrared spectroscopy, respectively [ 5 , 8 , 9 ] ( Table 1 ). Vincellete et al [ 8 ] investigated the effect of a two-week watermelon juice ingestion (500 mL–795 mg of L-citrulline) on attenuating acute hyperglycemia-induced vascular dysfunction in young healthy adults. It was observed that watermelon juice increased the postprandial FMD and microvascular blood flow area under the curve (AUC) (slope of the linear increase in total hemoglobin) compared to placebo.…”
Section: Evidence Of Watermelon Ingestion On Vascular Healthmentioning
confidence: 99%
See 3 more Smart Citations